THEORETICAL AND EXPERIMENTAL STUDY OF THERMAL CONTACT RESISTANCE EFFECT ON THERMOELECTRIC GENERATION USING PELTIER MODULES - Lisboa, Matheus Hoffman; Pimenta, João Manuel Dias (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
To meet the growing global demand for energy, new forms of power generation are of extreme importance, as well as increasing the efficiency of existing methods. The present study intends to model analytically the heat transfer through a thermoelectric generator (TEG) comprised by a Peltier module. The thermoelectric generation from these modules have promising future prospects, as they are light, small and targets of continuous improvement. Was designed the implementation of a TEG in a vehicular exhaust for recovery of thermal energy present in the exhausting gases. Aiming this application, many variables shown to be relevant: flow characteristics, use of heat sinks, their geometry and composition and, mainly, the description of the interface between the surfaces of the module and the heat sinks. In this interface, the contact thermal resistance is a function of mounting pressure, surface roughness and the presence of interstitial material. After modeling the heat transfer, was implemented a numerical code to assess the sensitivity of the output voltage and contact resistance of the module with changes in the TEG operating conditions. Furthermore, to evaluate the simulated results, was developed an experimental bench reproducing TEG operating conditions, under the effect of different temperatures, flow velocities, contact pressures, roughness and interstitial material. With the use of only one module, the theoretical values for the output voltage was in the range of 0.92V and 0.97V for the worst and best case respectively,and the values of experimental measurements under the same operating conditions provided 0.75V and 1.07V. The discrepancy found between the theoretical and experimental approach resulted in a maximum relative error of 22.7%. The best output voltage values were obtained when minimized the thermal contact resistance, indicating that this is a way to increase the efficiency of a TEG and help meet the current demand of energy.